Mortality in patients with testicular cancer: report of the Anglia and Trent testicular tumour groups. Issue 6521 (8th March 1986) - Ellis, M; Sikora, K
Abstract : The overall prognosis of patients with testicular cancer has improved dramatically over the past decade. Most patients are now treated in regional oncology centres in general hospitals. The cause of death was determined in 52 patients in the East Anglian and Trent regions who presented between 1980 and 1984. The overall mortality was 10.8%. Thirty four patients died with progressive disease, 12 of treatment related problems, two suddenly at home in between chemotherapy courses, and four of incidental causes. Reasons for treatment failure and for the deaths related to treatment were analysed and several recommendations made to reduce the death rate in this highly curable disease predominantly of young men.